Hubungan Antara Umur dan Lama Paparan Dengan Penurunan Daya Dengar Pada Pekerja Terpapar Kebisingan Impulsif Berulang di Sentra Industri Pande Besi Desa Padas Karanganom Kabupaten Klaten - Ubaidilah, Kholid, Tarwaka, PGDip Sc, M.Erg, Dwi Astuti, SKM., M.Kes (2015)
Repetitive impulsive noise with high intensity and occur continuously can cause damage of the sense hearing. Such damage can be reduced hearing. The purpose of this study was to determine the relationship between age and duration of exposure with reduced hearing in workers exposed to repetitive impulsive noise in Sentra Industri Pande Besi Desa Padas Karanganom Kabupaten Klaten. This research method using observational design with cross sectional approach. The study population was all exposed workers to repetitive impulsive noise on the forging state. Selection of the sample is total sampling by all workers in the forging which was 30 people totally. Statistical test used Pearson Product Moment Correlation with statistics program. The results showed that there was a relationship between age and hearing impairment in both ears, p = 0.019 and r = 0.426 for the right ear with moderate relationship and p = 0.003 with r = 0.517 for the left ear with a strong relationship level. And there were very significant and strong correlation between long exposure with reduced hearing in both ears, p = 0.001 and r = 0.588 for the right ear and p = 0.000 with r = 0.620 for the left ear. Keywords : Age, length of exposure, reduced hearing, repetitive impulsive